Preliminary Study of Eels (Anguilla) in Sumbawa Island According to the Knowledge of Local Communities: Distributions, Pattern of Fishing, and Utilizations - Neri Kautsari; Husain Latuconsina; Ilham Zulfahmi (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research The biodiversity, distribution and capture of eels on Sumbawa Island are traced through local community knowledge There are four types of eels in Sumbawa, namely marmorata, A. celebensis, A. interioris, A. bicolor Eels are found in rivers, dams, estuaries and rice fields Eel is not the main catch Eel fishing by the community is carried out because the hobby of fishing is not for livelihood In general, people do not know about eel conservation in Indonesia Abstract Eels are an important fishery resource in Indonesia, but information regarding distribution, fishing patterns and utilization has not been well documented in order for it to assist in the management of eel fisheries. One of the areas in Indonesia that uses eels is the Sumbawa Island community. The local community knowledge approach is an important for fisheries management, because it is an inherent component of fishery resources. This is preliminary study of eels in Sumbawa Island. This study aimed to examine the distribution, pattern of fishing, and utilization of eels from knowledge of local communities. Data were taken through in-depth interviews with 166 respondents. The study was conducted from November to December 2021. Interviews were conducted to obtain information and knowledge from local communities about eels (locations where they were eels found, fishing gear used, time, season and, utilization of eel, and community knowledge regarding its protection status). The results showed that the eels are found in dams, rivers, and estuaries. Most eels were caught from November to December in rainy season. Most people catch eels out of a hobby. Fishing rods and stuns are the two main fishing tools used to catch eels. There are three types of eel utilization, namely (1) consumed, (2) distributed to family and neighbors, and (3) marketed. Respondents (83.64%) did not know about the limited protection for several species of eels.